GENETIC DIVERSITY OF INTERSPECIFIC HYBRIDS OF THE GENUS ALLIUM L. - V. S. Romanov; L. Yu. Kan; A. S. Domblides; N. I. Timin; L. K. Gurkina; M. M. Tareeva (Овощи России)
Selection based on interspecific hybridization of fundamentally new plant forms with a unique combination of genetic material allows expanding the scope of genotypic and phenotypic variability. In this work the comparative analysis of plants of interspecific hybrids of genus Allium L. from various inbred descendants of combinations of crossing of species A. cepa х A. vavilovii and A. cepa х A. fistulosum on selection traits is carried out.Forms were identified: by mass of the bulb more than 100 g; with contrasting coloration of dry cover scales bulbs; by the index of the shape of the bulb; on the resistance to peronosporosis of plants of the first year of vegetation and seed plants; by the number of arrows; height of the arrow; on seed production with a sufficiently high percentage of fertile plants. Plants of interspecific hybrids of onions formed bulbs weighing from 20 to 120 g, with white, golden-yellow, dark golden-yellow, brownish and dark purple color of dry covering scales of a bulb. Plants of interspecific hybrids of onions were flat and round-flat shape of the bulb with the frequency of symptoms ranging from 6.9 to 93.3% and from 11.7 to 93.3%. In a phytopathological evaluation of interspecific hybrids of onions the first year of vegetation identified plants with resistance to downy mildew is from 0 to 4.0 points. Was studied the frequency of occurrence of plants in the progenies weight, colour, bulb type, number, height of the seedstalk, seed productivity and resistance to downy mildew. The increase of genetic diversity in onion plants obtained on the basis of interspecific hybridization, backcrossing and inbreeding is shown.